Plethysms and interacting boson models - Alcaras, JAC; Tambergs, J.; Krasta, T.; Ruza, J.; Katkevicius, O. (American Institute of Physics (AIP), 2003)
A short review of the plethysm technique aiming to its application in finding branching rules for the reduction of an irreducible representation of a group under the restriction to one of its subgroups is given. The algebraic structure of the interacting boson model and some of its extensions is given together with the branching rules needed to classify their basis states, obtained by the use of plethysms. (C) 2003 American Institute of Physics.